Does the width of the surgical margin of safety or premalignant dermatoses at the negative surgical margin affect outcome in surgically treated penile cancer?. Issue 3 (7th October 2013) - Gunia, Sven; Koch, Stefan; Jain, Anjun; May, Matthias
Abstract : Aims: To evaluate the prognostic impact of the width of negative surgical margins (NSM) and associated and preinvasive lesions at the NSM in patients with penile squamous cell cancer (PSC). Methods: Enrolling 87 patients with NSM who underwent surgery for PSC, the archived margin slides and entirely wax-embedded surgical margins were retrieved from the pathology files. After step sections were cut, margins were stained with antibodies against CK5/6, p16, p53 and Ki-67 and subjected to in situ hybridisation for high-risk human papillomavirus (HPV). All NSM were histologically examined for squamous hyperplasia (SH), lichen sclerosus (LS) and subtypes of penile intraepithelial neoplasia (PeIN). Then, histological findings were correlated with cancer-specific mortality (CSM, median follow-up 34 months; IQR 6–70). Results: All NSM were negative for high-risk HPV and exhibited SH (p16 and p53 negative, Ki-67 variably positive), LS (p16 negative, variable p53 and Ki-67 positivity) and differentiated PeIN (dPeIN; p16 negative, Ki-67 positive, variable p53 positivity) in 28 (32%), 30 (34%) and 22 (25%) cases, respectively, whereas PeIN subtypes other then dPeIN did not occur. Pathological tumour stage was the only independent predictive parameter with respect to CSM in the multivariable analysis (p=0.001). Conclusions: SH, LS and dPeIN are frequent histological findings at the NSM of surgically treated PSC. However, neither the width of the NSM nor dPeIN, LS or SH at the NSM influences prognostic outcome.